Mitigating Snell’s-Law Reflection and Transmission with Metasurfaces of Ordinary Dielectrics - Tsitsas, N. L.; Valagiannopoulos, Constantinos (IEEE, 2017)
Obtaining anomalous reflection and transmission (namely propagation along directions different from those predicted by Snell’s law) is investigated for plane waves impinging on a planar periodic metasurface composed of two dielectric layers. The associated boundary-value problem is treated by a rigorous entire-domain integral equation methodology. Optimizations with respect to the con- figuration’s parameters are performed which reveal that it is possible to obtain significantly enhanced anomalous transmission and reflection depending on the color of the incident light. The optimal parameter values correspond to metasurfaces which can be easily realizable by low-loss dielectric materials.
Keywords: Snell’s-Law; ordinary dielectrics; Research Subject Categories::NATURAL SCIENCES::Physics